2020
DOI: 10.4103/ijmbs.ijmbs_2_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between high- and low-risk diabetic patients who fast Ramadan: A prospective cohort study

Abstract: Objectives: The aim of this study is to compare the low-risk patients with the high- and very high-risk patients who choose to fast during Ramadan regarding the rates of breakfasting, hypoglycemia, hyperglycemia, hospitalization, and death. Patients and Methods: This is an observational, analytic, 1-month prospective, cohort study that involved patients with diabetes mellitus who choose to fast during the month of Ramadan in the Muslim year 1437. The patients were divided into two cohorts: Cohort 1 (high-risk)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the current issue of Ibnosina Journal of Medicine and Biomedical Sciences, Elbarsha et al from Benghazi, Libya, compare the impact of fasting during Ramadan in a prospective observational study on the low and high-risk groups. [15] This study enriches the literature from several studies that have addressed the same theme and warrants highlighting the recent developments as they were not discussed in detail in the manuscript. Among the participants, 83 high-risk patients were categorized as "high/very high-risk" and 65 low-risk patients were categorized as "moderate/low risk".…”
mentioning
confidence: 77%
“…In the current issue of Ibnosina Journal of Medicine and Biomedical Sciences, Elbarsha et al from Benghazi, Libya, compare the impact of fasting during Ramadan in a prospective observational study on the low and high-risk groups. [15] This study enriches the literature from several studies that have addressed the same theme and warrants highlighting the recent developments as they were not discussed in detail in the manuscript. Among the participants, 83 high-risk patients were categorized as "high/very high-risk" and 65 low-risk patients were categorized as "moderate/low risk".…”
mentioning
confidence: 77%
“… 4 A Libyan study reported that 22% of individuals with diabetes broke their fast for a day or two because of health concerns. 21 …”
Section: Discussionmentioning
confidence: 99%
“…4 A Libyan study reported that 22% of individuals with diabetes broke their fast for a day or two because of health concerns. 21 Individuals with diabetes appear to perform less SMBG during Ramadan and avoid managing post-Iftar BG, which is the primary meal and source of glycaemic spikes. Our study results emphasise the importance of SMBG in avoiding sudden fluctuations in BG among individuals with diabetes; particularly, those who have diabetic complications should be more cautious while keeping their fast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbarsha et al report a comparison between high-and low-risk diabetic patients who choose to observe the fasting of Ramadan in a prospective cohort study from Benghazi, Libya. [9] Rare, unusual, or simply illustrative case reports remain a regular feature of the journal. In this issue, three case reports are included: (1) early-onset antibiotic-induced autoimmune hemolytic anemia, (2) a rare case of intra-auricular sinus presenting as recurrent perichondritis, and (3) urinary diversion in patients with muscle-invasive bladder cancer and severe ureteral stricture -A case report of a new surgical technique.…”
mentioning
confidence: 99%